Benefits of E-Learning in Learning Civic Education - Hanifah Wadawiyah (International Journal of Students Education, 2024)
Research purposes this is for know utilization of e-learning in learning especially in Citizenship Education learning this study investigate utilization of e-learning in learning education citizenship. Method used is literature review systematics with instrument collection the data through observation, documentation, and literacy. Research result this showing that e-learning is very useful in current online learning this so that students and lecturers start used to with non- face- to-face learning advance or learning distance away and study case from implementation of e-learning in context education citizenship in various countries. Findings show that e- learning can increase accessibility, flexibility, and interactivity in learning citizenship. However, challenges like lack of internet accessibility and lack thereof involvement student need overcome for maximizing potential of e- learning in increase understanding and participation citizenship student.